Spontaneous Vestibular Schwannoma Regression: A Case-Control Study. Issue 10 (December 2018) - Tikka, Theofano; Yiannakis, Constantina P.; Stapleton, Emma; Locke, Richard; Crowther, John A.; Taylor, William A. S.; Kontorinis, Georgios
Abstract : Objective: To explore the nature of spontaneously regressing vestibular schwannomas (VS) and identify possible predictive factors for such behavior. Study Design: Retrospective case control study. Setting: Tertiary referral center, university teaching hospital. Patients: Patients with sporadic VS demonstrating spontaneous regression compared with a control group of patients with growing VS. Interventions: Review of serial magnetic resonance imaging of the internal auditory meatus (MRI IAM) and case notes and direct comparison of possible related factors between the two groups using univariate analysis. Main Outcome Measures: Presenting symptoms, VS size and consistency, patients' age and sex, tumor laterality and location, and the neutrophil-to-lymphocyte ratio between the two groups. Results: Of the 540 patients on the database 28 (5.2%) showed spontaneous regression with a mean follow-up of 122 months. Mean absolute and relative regression was 3.9 mm and 25.7%, respectively. 60% of tumors showed gradual regression while 25% showed growth followed by regression. Regressing VS had a significantly larger size than the control group; while the regressing tumors were located further from the fundus than the control group. The remaining examined factors did not reach a statistical level of significance. Conclusion: This is, to our knowledge, the first study comparing a cohort of regressing tumors with a control group of growing VS. The finding that the location of tumors around the porous, is more common in regressing VS has implications for patients' counselling.